Dexmedetomidine combined with sufentanil and dezocine-based patient-controlled intravenous analgesia increases female patients’ global satisfaction degree after thoracoscopic surgery - Qiongzhen Li (Journal of Cardiothoracic Surgery, 2021)
Abstract Background There are no studies on the use of dexmedetomidine combined with sufentanil and dezocine-based patient-controlled intravenous analgesia (PCIA) in females undergoing thoracic surgery. We postulate that introducing dexmedetomidine to a combination of dezocine-based PCA drugs and sufentanil will increase female patients’ global satisfaction degree. Methods One hundred fifty-two female patients with physical classification type I or II according to the American Society of Anesthesiologists undergoing thoracoscopic surgery were arbitrarily classified into two categories, either receiving sufentanil and dezocine-based PCIA (group C) or incorporating dexmedetomidine with sufentanil and dezocine-based PCIA (group D). The patients’ global satisfaction degree, postoperative nausea and vomiting (PONV), PCA bolus, rescue analgesia requirements, drug-related adverse effects, rest and coughing visual analogue scale (VAS) ratings, and Ramsay sedation scores (RSS) were measured at 6, 12, 24, 36 and 48 h after surgery. Results Compared with the C group, the patient satisfaction degree was significantly higher; pain scores at rest and coughing were significantly different at 6, 12, 24, 36 and 48 h postoperatively; less rescue analgesia and PCA bolus were required; and a lower incidence of PONV was found in the D group. There were non-significant trends for the sedation scores and drug-related adverse effects in both groups. Conclusions Dexmedetomidine combined with sufentanil and dezocine increased female patients’ global satisfaction degree after thoracoscopic surgery. This effect could be linked to the improvement in postoperative analgesia and reduction in postoperative nausea and vomiting; the combined treatment did not increase drug-related adverse effects in female patients. Trial registration Chinese Clinical Trial Registry number, ChiCTR2000030429 . Registered on March 1, 2020.